Perspectives on DMPA-SC for self-injection among adolescents with unmet need for contraception in Malawi - Ali, Gracious; Porter Erlank, Chelsey; Birhanu, Frehiwot; Stanley, Melinda; Chirwa, Jessie; Kachale, Fannie; Gunda, Andrews (Frontiers in Global Women's Health, 2023)
Introduction Malawi has made progress in expanding access to modern contraceptive methods over the last decade, including the introduction of depot-medroxyprogesterone acetate subcutaneous (DMPA-SC) in 2018. DMPA-SC offers women the option to self-inject at home and may benefit adolescents with unmet need for contraception due to its discretion. This qualitative study was conducted to assess perspectives and preferences of adolescents with unmet need for contraception regarding the self-injection option of DMPA-SC in Malawi. Methods Six focus group discussions were conducted involving 36 adolescents with unmet need for contraception (aged between 15 and 19 years, married and never-married) in October 2021 in three districts in Malawi. Data were coded inductively and analyzed thematically, using Dedoose software. Two validation workshops were conducted with other adolescents with unmet need in February 2022 to elucidate the preliminary findings. Results DMPA-SC attributes such as discretion and reduced facility visits were ranked most appealing by both married and never-married adolescents, particularly for adolescents needing covert contraception use. Concerns about self-injection included fear of pain, injury, and doubt in ability to self-inject. Never-married adolescents had additional concerns around privacy at home if using covertly, and fears of affecting long-term fertility. Overall, health surveillance assistants (community-based healthcare workers) were voted to be the most private, convenient, and affordable sources for potential DMPA-SC self-injection training. Conclusion Self-injection of DMPA-SC may offer an appealing option for adolescents in Malawi, aligning most closely to the needs of married adolescents who may wish to delay or space pregnancies conveniently and discreetly, and who also may face fewer access barriers to receiving self-injection training from health care providers. Access barriers including stigma and concerns about privacy at home for adolescents needing to use contraception covertly would need to be adequately addressed if never-married adolescents were to consider taking up this option.